Relationships rights and legal pluralism
1 online resource
Keywords: "This interdisciplinary book brings together leading social and legal scholars to tackle the incompatibility of marriage laws with contemporary social reality in Europe. Their critique is based on the assumption that individuals should be able to choose how they organise their close relationships. The contributors emphasise the importance of pluralism of beliefs, values, cultures and lifestyles and the consequent need for legal recognition to make individuals' private choices valid and respected. The first part of the book establishes the foundation for the subsequent chapters by exploring the advantages and challenges of focusing on values while accommodating relationship design plurality, the impact of the European Court of Human Rights on the issue and the transformation of the institution of marriage. The second part presents different legal responses to non-state marriages, particularly religious marriages in Muslim communities, and proposals for reform. The third part of the book features empirical research on the marital experiences of two communities: Muslims and migrants. The chapters concentrate on polygyny among female converts to Islam, the importance of religious knowledge for practicing Muslim women to secure rights in their marital relationships, transnational and interreligious marriages and the impact of acculturative orientation and position in the dual labour market on the choice of life partner among Polish migrant women. The book will be of interest to academics, researchers and policy-makers working in the areas of human rights law, family law, legal anthropology, law and religion, socio-legal studies, feminism and queer studies and sociology of family"--